The experience and the creation in the air traffic control labour - Itani, Alice [UNESP] (Rede Investigacao Condicoes Trabalho-ricot, 2018)
Is there perspective of the creation in the work developed under standards and strict rules and time pressure? This paper aims to analyze the experience of the air traffic controllers, by analyzing the data carried out with air traffic controllers in Sao Paulo and Rio de Janeiro. These activity is developed using process, images and mental representations There is effort and commitment to develop this activity to account for an employment density. But, when it is analyzing the air traffic controllers in their activity, it verify some actions to improve the activity. These strategies are developed based on structure of guidance and knowledge network to create another process, which is appropriate by the workers. Such strategies can be considered as creation.
Keywords: air traffic controller; aviation; health; cognitive effort; creation